Identidade e morte: um possível vir a ser a partir da ausência - Santos, Marcelo Alves dos (2019)
The objective of this thesis is to discuss the relation between Human Identity and the impact that death could have on it. We intend to investigate how the identity process and the reorganization of the life project occur after the unveiling, adjustment and metamorphosis of the Identity of deceased people. In this context, our main focus is on the syntagma identity-metamorphosis-emancipation within the Identity theory proposed by Antonio da Costa Ciampa. It is our understanding that an individual’s identity is not stable, it is constantly changed and reconstructed while representing social roles, be it by interacting with one another or through everyday situations. Despite being a taboo in many cultures, death will always be a major event that takes place in every single group of people. Therefore, all considerations and their relation to social psychology demanded interdisciplinary efforts since death is very particular to each culture. In this case, we allude to what death represents in the Brazilian culture. It is our understanding that the awareness of death could cause existential anxiety, leading human beings to search for the meaning of life. The thesis is arranged in three chapters. Chapter 1 – Prelude: a continuous self-reflection. In this chapter we discuss the beginning of a story in which the researcher is the main character and the reasons that led him to study Identity and Death. Subsequently, we introduce the topic and its connection with the Identity Theory developed by Professor Dr. Ciampa. We present our research methods; the history of the Colônia Psychiatric Hospital in Barbacena – MG – Brazil and its historical relevance to the Psychiatric Reform in Brazil. Chapter 2 – Interlude: a potential “come to be” from absence. In this chapter, we present the concept and background of the subject Death and its relation to the Identity Theory. Afterwards, we introduce a new character, Sueli, and the impacts that being admitted to the largest Psychiatric Hospital in Brazil caused on her Identity, as well as her contribution to her daughter Débora’s Identity subsequent to the unveiling of her post mortem story. Still in this chapter we conduct a deeper analysis of these questions based on the work of José Roberto Malufe. Chapter 3 – Postlude: human metamorphosis. We focus on presenting Débora’s life story narrative. The analysis of her story made it possible for us to observe each transformational act in her life after the unveiling of her deceased biological mother’s life story. Through our findings, we were able to comprehend how the identity of a deceased person affects the search for the meaning of life of a living person. Furthermore, the results of the study contributed to the continuous development of the Identity Theory studied by the Núcleo de Estudos e Pesquisa sobre Identidade e Metamorfose (NEPIM – PUC/SP), currently led by Professora Dra Cecilia Pescatore Alves